The future of charity marketing - Mitchell, Sarah-Louise, 1966-; Hyde, Fran, 1969- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
Charities play an increasingly important role in our society. Whether caring for the vulnerable, campaigning for change or enabling access to the arts, they are organisations on a mission, underpinned by social purpose. However, charities now face unique challenges in a turbulent global economic climate due to structural changes in society post Covid and pressure on disposable incomes. Charities need to transform and, in some cases, modernise for sustained increasing demand from their service users. They need to engage with a wider range of stakeholders, meet higher public expectations on transparency and governance and compete for resources from existing as well as a continuous range of new competitors. This book brings together leading scholars to think about what is needed to future proof the nonprofit sector in areas such as partnerships, collaborations, branding, communications, income generation and fundraising, stakeholder involvement and meeting the future needs of service users.This edited collection builds upon the research in the editors' first book Charity Marketing: Contemporary Issues, Research and Practice to challenge students, researchers and practitioners in understanding the challenges and opportunities ahead and think about how to future proof nonprofit marketing. Drawing from a diverse group of academics and deep-thinking practitioners, The Future of Charity Marketing focuses on how charities can prepare for the future through sharing big ideas and examples of best practice. Presenting contrasting perspectives and the latest thinking on a range of challenges, this book gives topics for classroom debate, identifies areas for future research and offers practitioners useful insights.
Keywords: Charities -- Marketing; Marketing; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Marketing / Research; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities